Role of MAP kinases in regulating expression of antioxidants and inflammatory mediators in mouse keratinocytes following exposure to the half mustard, 2-chloroethyl ethyl sulfide - Black, Adrienne T. (2010)
Dermal exposure to sulfur mustard causes inflammation and tissue injury. This is associated with changes in expression of antioxidants and eicosanoids which contribute to oxidative stress and toxicity. In the present studies we analyzed mechanisms regulating expression of these mediators using an in vitro skin construct model in which mouse keratinocytes were grown at an air-liquid interface and exposed directly to 2-chloroethyl ethyl sulfide (CEES), a model sulfur mustard vesicant. CEES (100-1000 μM) was found to cause marked increases in keratinocyte protein carbonyls, a marker of oxidative stress. This was correlated with increases in expression of Cu,Zn superoxide dismutase, catalase, thioredoxin reductase and the glutathione-S-transferases, GSTA1-2, GSTP1 and mGST2. CEES also upregulated several enzymes important in the synthesis of prostaglandins and leukotrienes including cyclooxygenase-2 (COX-2), microsomal prostaglandin E synthase-2 (mPGES-2), prostaglandin D synthase (PGDS), 5-lipoxygenase (5-LOX), leukotriene A(4) (LTA(4)) hydrolase and leukotriene C(4) (LTC(4)) synthase. CEES readily activated keratinocyte JNK and p38 MAP kinases, signaling pathways which are known to regulate expression of antioxidants, as well as prostaglandin and leukotriene synthases. Inhibition of p38 MAP kinase suppressed CEES-induced expression of GSTA1-2, COX-2, mPGES-2, PGDS, 5-LOX, LTA(4) hydrolase and LTC(4) synthase, while JNK inhibition blocked PGDS and GSTP1. These data indicate that CEES modulates expression of antioxidants and enzymes producing inflammatory mediators by distinct mechanisms. Increases in antioxidants may be an adaptive process to limit tissue damage. Inhibiting the capacity of keratinocytes to generate eicosanoids may be important in limiting inflammation and protecting the skin from vesicant-induced oxidative stress and injury.